2015
DOI: 10.1002/pip.2583
|View full text |Cite
|
Sign up to set email alerts
|

A monolithically integrated high‐efficiency Cu(In,Ga)Se2 mini‐module structured solely by laser

Abstract: Monolithically integrated Cu(In,Ga)Se2 mini‐modules were fabricated in order to reduce the width of patterning related dead area. The Cu(In,Ga)Se2 layers were prepared on soda‐lime glasses using the multistage process at low substrate temperature below 500 °C. A picosecond laser with a wavelength of 532 nm was used for all of the structuring processes (P1, P2, and P3) for the monolithic integration. A “lift‐off” type structuring was applied for P1 and P3, and an “ablation” type was for P2. The laser structurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…It should be emphasized that most of the shown PV technologies cannot sustain the required voltage of 1.7 V without a series connection. With our design concept, large area, scalable, efficient photovoltaic water-splitting devices are feasible for all thin-film PV technologies where a series connection can be realized, for example, by laser processing 51 52 53 54 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that most of the shown PV technologies cannot sustain the required voltage of 1.7 V without a series connection. With our design concept, large area, scalable, efficient photovoltaic water-splitting devices are feasible for all thin-film PV technologies where a series connection can be realized, for example, by laser processing 51 52 53 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the light microscope images of electrically optimized processes before back contact deposition. It can be seen that although rather low contact resistance values are achieved for the three processes, their geometrical extent or scribe width is quite different and quite high for 532 nm, when compared to optimized processes for thin‐film silicon or CIGS, which would lead to increased active area losses and thus, to an overall performance decrease. To identify the impact of the contact resistance and scribe width of the P2 process on the solar module performance, electrical modeling is required.…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the P2 contact resistance processing in a high pulse energy, low ambient pressure regime conditions can help to massively reduce the amount of redeposition . Furthermore, for solar cell materials with a similar ablation behavior, it is known that the use of ultra‐short pulsed lasers can lead to low P2 contact resistances …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies [1,2] we investigated various scribing process combinations and found optimum module performance when ultrashort pulsed lasers with pulse durations of tens of picoseconds were used. An efficiency of 16.6 percent (illuminated aperture) for an all-laser scribed mini module on 50x50 mm 2 float glass substrate was demonstrated [3]. The laser source used to realize said modules was the Katana HP fiber laser (Onefive GmbH, Switzerland) with maximum pulse energy of 15 µJ at 1064 nm.…”
Section: Introductionmentioning
confidence: 99%